Effect of Mating and Presence of Males on Reproductive Success and Lifespan of the Tribolium castaneum Female Beetles (Journal of Academic Research, 2023)
Tribolium castaneum is a polyandrous species, in which females mate multiply with the same male or different males. The frequency of mating in insects, including this species, is common and often beneficial to female reproductive output and longevity but also often costly behaviour. In this study, we investigated the effect of multiple mating on reproduction and longevity of this species by different mating protocols from using virgin females, once mated females, monogamy (each female kept with one male) to polyandry (each female kept with 5 males). This study found no evidence for the effects of multiple mating on the fecundity and egg hatching success of female T. castaneum at least over the first six days of oviposition. The number of mates to which females were exposed significantly affected female lifespan. Females kept with 5 males lived shorter than the other groups, while virgin females lived for longer than the groups. Our results suggest that the presence of many males with a female of T. castaneum is costly to the female since females which were kept with 5 males died earlier and produced less offspring than females were kept with one male each.